Simulation of vibrations of rectangular and square membranes using computer graphics - AROKIASAMY, A (2002)
The study of vibrations of membranes is of importance in connection with design of loudspeaker diaphragms, telephone receivers and microphones and many other acoustical devices but also non-acoustical devices like automobiles. For higher order modes of vibrations calculating and plotting the vibrations becomes difficult. But it is easy to simulate these vibrations in computer graphics. In this paper vibrations of rectangular membranes are simulated in different modes taking care of the boundary conditions. It is also possible to visualise the actual vibrations in the computer monitor by allowing the membrane to vibrate from a maximum to minimum amplitude. To simulate these vibrations, nowadays, simulation packages like Mathematica. Maple, MATLAB etc. are being used. Here, an attempt is made to simulate these vibrations using the Java programming language. (C) 2002 Elsevier Science B.V. All rights reserved.